Enhancing civil servants performance through technical competency development in Provincial Government of West Sulawesi, Indonesia - DP, Muhammad Idris; Rerung, Stevany Dwi Djulya; Mauliana, Deasy; Mustamin, Nur Afifah; Azmi, Ilima Fitri (Otoritas : Jurnal Ilmu Pemerintahan, 2025)
This study aims to determine the Technical Competency Development Plan at the Regional Civil Service Agency of West Sulawesi Province. This study uses a qualitative method with a descriptive approach to provide a realistic, logical, factual, and accurate picture of what is happening in the field. Data was collected through document review, observation, and interviews. The data obtained was then analyzed based on the National Institute of Public Administration Regulation No. 10 of 2018 on the Development of Civil Servant Competencies. The results showed that the inventory in the first stage, namely the completion of civil servant profiles, had not yet been carried out. The competency gap analysis as the second stage had also not been carried out because the job competency standards were still in the drafting stage. The third stage is performance gap analysis through the assessment of employee performance targets, where overall civil servants are rated as good, but competency improvement is considered necessary to support civil servant performance in achieving the maximum result, which is an excellent rating. Finally, the verification and validation stage has not been carried out due to the absence of documents outlining the planning needs for competency development.